Influence of the results of international studies on the choice of treatment tactics for unresectable forms of squamous cell carcinoma of the head and neck - L. V. Bolotina; T. I. Deshkina; A. L. Kornietskaya; S. A. Kravtsov; T. V. Ustinova; A. A. Paychadze; A. D. Kaprin; А. А. Fedenko (Опухоли головы и шеи)
The results of the clinical studies have a direct impact on clinical practice. The main criteria for the effectiveness of treatment method are increasing the overall life expectancy and improving its quality. In the treatment of common forms of squamous cell carcinoma of the head and neck, induction chemotherapy can be used, including platinum drugs, preferably in combination with cetuximab. Next immuno-oncological drugs should be prescribed. In the future, in the 1st line of therapy, it is possible to replace cetuximab with pembrolizumab or monotherapy with pembrolizumab, which allows to increase the effectiveness of treatment and reduce its toxicity. The article presents 3 clinical observations that demonstrate the possibility of integration the results of clinical research in practice.